Impact of psycho-social stress levels on clinical profile of acute central serous chorioretinopathy patients - Ashok Kumar; Sanjay Kumar Mishra; Vikas Ambiya; Ayon Gupta (Indonesian Vitreoretinal Society, 2020)
Introduction: To study the impact of the level of psycho-social stress on varied clinical presentations of acute Central serous chorioretinopathy (CSCR) patients. Methods: This prospective observational study included 83 patients with acute central serous chorioretinopathy who presented to our out-patient department. All confirmed cases of acute CSCR were subjected to a questionnaire based on social readjustment rating score which included 43 life events that analyzed if psycho-social stress contributed to their present illness. Patients underwent a comprehensive ocular evaluation including best corrected visual acuity, slit lamp examination of anterior segment, fundus examination using slit lamp with a contact lens or non-contact lens, indirect ophthalmoscopy, digital fundus photography, of Spectral Domain-Optical Coherence Tomogram(SD-OCT) and Fundus FluoresceinAngiography(FFA). The stress scores obtained were statistically analyzed with clinical and angiographic parameters obtained in patients. Results:A total of 83 patients were included in the present study. 72(86.74%) patients were males,the majority of them presenting with unilateral involvement (n=70; 84.33%). The prevalence of stress level was mild in 5(6.02%); moderate in 31(37.34%) and severe in 47(56.62%) subjects. Severe level of psycho-social stress was significantly associated with bilateral presentation of serous detachment in posterior pole of fundus (17/47; p-value=0.04)as well as multiple angiographic leaks on FFA(19/50; p-value=0.03). Conclusion:Higher levels of psycho-social stress can lead to more severe forms of presentation in acute CSCR with a possible sub-optimal visual recovery. Avoidance of stress and relaxation therapies can help in preventing severe forms of acute CSCR.